Persistence of seaweed forests in the anthropocene will depend on warming and marine heatwave profiles. Issue 1 (22nd December 2021) - Straub, Sandra C.; Wernberg, Thomas; Marzinelli, Ezequiel M.; Vergés, Adriana; Kelaher, Brendan P.; Coleman, Melinda A.
Abstract : Marine heatwaves (MHWs), discrete periods of extreme warm water temperatures superimposed onto persistent ocean warming, have increased in frequency and significantly disrupted marine ecosystems. While field observations on the ecological consequences of MHWs are growing, a mechanistic understanding of their direct effects is rare. We conducted an outdoor tank experiment testing how different thermal stressor profiles impacted the ecophysiological performance of three dominant forest‐forming seaweeds. Four thermal scenarios were tested: contemporary summer temperature (22°C), low persistent warming (24°C), a discrete MHW (22–27°C), and temperature variability followed by a MHW (22–24°C, 22–27°C). The physiological performance of seaweeds was strongly related to thermal profile and varied among species, with the highest temperature not always having the strongest effect. MHWs were highly detrimental for the fucoid Phyllospora comosa, whereas the laminarian kelp Ecklonia radiata showed sensitivity to extended thermal stress and demonstrated a cumulative temperature threshold. The fucoid Sargassum linearifolium showed resilience, albeit with signs of decline with bleached and degraded fronds, under all conditions, with stronger decline under stable control and warming conditions. The varying responses of these three co‐occurring forest‐forming seaweeds under different temperature scenarios suggests that the impact of ocean warming on near shore ecosystems may be complex and will depend on the specific thermal profile of rising water temperatures relative to the vulnerability of different species.